Effects on Yield and Nutrient Concentration of Spinach (Basella Alba L.) At Different Salinity Levels - Alam Tarafder, Md Mahbubul; Khan, Mahbubr Rahman; Tasmin, Sadia; Rahman , Md Habibur (Bangladesh Journal of Botany, 2023)
Effects of salinity and nutrient concentration were examined for spinach (Basellaalba L.) in pot culture at glass house of the Institute of Agricultural Resource and Regional Planning (IARRP), CAAS, Beijing, China during March to April 2018.There were four levels of salinity (viz. 0, 4, 8 and 16 dSm-1) as treatment for the trial. The salt stress significantly affected the total biomass weight and the lowest biomass production was found at highest salinity level. Although the photosynthetic rate decreased with increasing salt stress but no significant effect was observed between 12 and 16 dSm-1 salinity level. But a noticeable salinity levels up to 8 dSm-1 showed a better trend in photosynthesis rate. The total nitrogen in soil reduced from 97.9 to 28.1 mg kg-1 when salinity increased to 16 dSm-1 and total phosphorus showed similar trend and availability reduced 667.3 to 519.3 mg kg-1. Both nitrogen and sodium became more available for plant in saline condition. The potassium increased from 2811.7 to 5640.3 mg kg-1 when salinity level was 16 dSm-1 and sodium showed similar trend and availability increased to 1.4 to 3.5 mg kg-1. Nutritional disorder occurs due to salt stress, thus adversely affected on nutrient concentration, uptake and transport in plant and affected negatively on the yield of spinach. Bangladesh J. Bot. 52(1): 71-77, 2023 (March)